A prediction-based scheduling mechanism for interconnection between WiMax and satellite networks. (6th April 2009) - Lygizou, Anastasia; Xergias, Spyros; Passas, Nikos; Merakos, Lazaros
In this article, we describe and evaluate a scheduling mechanism that can be used in joint WiMax/satellite environments. The proposed mechanism consists of three parts. The first part requests satellite bandwidth based on an estimation of the needs of the WiMax network at the time the bandwidth is granted, the second part allocates bandwidth on the satellite channel, while the third distributes it to the WiMax users. Simulation results show considerably improved performance compared to a simpler mechanism without prediction, especially in terms of throughput and delay.